Autonomy of Patients With Type 2 Diabetes With an Insulin Pump Device: Is It Predictable?. (July 2014) - Reznik, Yves; Morello, Rémy; Zenia, Amel; Morera, Julia; Rod, Anne; Joubert, Michael
Background: Insulin pump therapy may be offered to patients with type 2 diabetes that is not controlled by multiple daily injections. Patients with type 2 diabetes may suffer from unrecognized cognitive disabilities, which may compromise the use of a pump device. Methods: To predict patient autonomy, we evaluated 39 patients with type 2 diabetes from our database (n = 143) after continuous subcutaneous insulin infusion (CSII) initiation using (1) an autonomy questionnaire evaluating the patient's cognitive and operative capacities for CSII utilization, (2) the Montreal Cognitive Assessment (MOCA) for the detection of mild cognitive disabilities, (3) the Hospital Anxiety and Depression Scale (HADS) for the detection of anxiety and depression, and (4) the Diabetes Treatment Satisfaction Questionnaire (DTSQ). Patients were selected to constitute 3 groups matched for age, with different degrees of autonomy at discharge after the initial training program: complete (n = 13), partial (n = 13), or no autonomy (n = 13). Results: The satisfaction level with the pump device was high. At the last follow-up visit, only 23% of patients did not reach complete autonomy. The autonomy score correlated fairly with the MOCA score ( R = 0.771, P < .001). A receiver operating characteristic (ROC) analysis showed that at a cut-off score of 24, the MOCA identified autonomous versus dependent patients at long-term follow-up (area under the ROC curve [AUC], 0.893; sensitivity, 81%; specificity, 81%). The HADS correlated negatively with the autonomy score, and the sociocultural level also influenced autonomy with pump utilization. Conclusion: Patients with type 2 diabetes with partial autonomy at discharge may progress to complete autonomy. The MOCA and HADS may help predict a patient's ability to manage with a pump device.